Nutritional Content of Milkfish Nuggets with Addition of Mocaf Flour - Aniq Luthfiyah; Purbowati .; Riva Mustika Anugrah (Universitas Pendidikan Indonesia, 2021)
Milkfish is protein source. Utilization of milkfish is not easy because has lot of fish bones. Processing milkfish into nuggets could increase the acceptability of consumption. The addition of mocaf flour also increases local food commodities which add to the nutritional value of milkfish nuggets. This study aims to determine the nutritional content of protein, fat, carbohydrates, calcium milkfish nuggets with the addition of mocaf flour. Pre-experimental research design. There are 3 formulations of milkfish nuggets with a ratio of milkfish and mocaf flour, namely F1 (80%: 20%), F2 (70%: 30%), F3 (60%: 40%), then the nutritional content test was carried out. Analysis of protein content by micro kjehdal method, fat by Soxhlet, carbohydrates by calculation by deference, and calcium by AAS. The protein content of milkfish nuggets F1, F2, F3 respectively were 15.02%, 14.58%, 13.25%. The fat content of F1, F2, F3 is 12.89%, 11.53%, 10.76%. The carbohydrate content of F1, F2, F3 is 23.63%, 31.44%, 33.95%. The calcium content of F1, F2, F3 is 0.041%, 0.051%, 0.052%. Of the three milkfish nugget formulas, the nutritional content in F1 meets the quality requirements of SNI No. 7758:2013 fish nuggets.